Application of Asmaul Husnah Dhikr Therapy to Reduce Anxiety Levels in Hypertension Patients with Anxiety Nursing Problems in the Nakula Ward of Jombang Regional Hospital - Dewi Suryawati; H. Arif Wijaya; Sudarsono; Agus Priyanto; Dina Camellia; Tiara Fatma (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension is a condition in which a person's blood pressure is above 140/90 mmHg, increasing the risk of serious illnesses such as stroke, heart attack, and kidney failure. It is often associated with psychological problems such as anxiety. One non-pharmacological approach to managing anxiety in hypertensive patients is Asmaul Husna remembrance therapy. The purpose of this study was to assess the implementation of nursing care for hypertensive patients with anxiety problems in the Nakula Room of Jombang Regional General Hospital through Asmaul Husna remembrance therapy. This study used a case study approach with a nursing care approach, with two hypertensive patients with anxiety problems as subjects. The study was conducted for 3 days using data collection methods including assessment, diagnosis, intervention, implementation, and evaluation. The results of the study showed a decrease in anxiety in both patients on the third day. The first patient was able to sleep peacefully last night, while the second patient began to calm down and stop thinking about her illness. The conclusion from the results obtained regarding the application of Asmaul Husna dhikr therapy is proven effective in reducing anxiety levels in hypertension patients in the Nakula Ward of Jombang Regional Hospital. Further research can be conducted to assess the long-term effectiveness of dhikr therapy and explore the application of other spiritual therapies in addressing anxiety in hypertension.